The Mediating Effect of Emotive Factor on the Constructs That Influence Entrepreneurial Failure - Hafiz Rahman; Eri Besra; Nurhayati Nurhayati (DeReMa (Development Research of Management): Jurnal Manajemen, 2019)
This paper examines the presence of emotive factor that mediates the variables of voluntaristic, deterministic and opportunistic behaviour that impact entrepreneurial failure. The study is a quantitative study and uses causal analysis as its research approach. It relates the constructs of voluntaristic factor, deterministic factor, and opportunistic behaviour with the mediation of emotive factor to entrepreneurial failure. Sample of the study is 1541 nascent entrepreneurs in West Sumatra Province, Indonesia, who have experienced business failures. Analysis was undertaken by using causal step analysis in which the statistical protocol and rule were operated. The study found and argue that emotive factor of entrepreneurs is identified as individual psychological construct that partially mediates voluntaristic, deterministic and opportunistic behaviour in causing entrepreneurial failure experienced by nascent entrepreneurs. Originality and value of the study lies in the framework used – which considers the construct of opportunistic behaviour of entrepreneurs as an independent variable that can cause entrepreneurial failure. Other is related to the consideration that emotive factor that mediates the voluntaristic, deterministic and opportunistic behaviour in causing entrepreneurial failure.Abstrak dalam Bahasa Indonesia Penelitian ini membahas tentang keberadaan faktor emosi yang memediasi variabel voluntaristic, deterministic dan perilaku opportunis yang mengakibatkan terjadinya kegagalan berwirausaha. Studi ini merupakan studi kuantitatif dan menggunakan analisa kausal sebagai pendekatan penelitian. Sampel penelitian sebanyak 1541 orang wirausahawan pemula di Provinsi Sumatera Barat, Indonesia yang sebelumnya pernah mengalami kegagalan dalam berwirausaha. Analisa dilakukan dengan menggunakan causal step analysis yang menggunakan prosedur statistik tertentu. Studi ini menemukan dan lebih lanjut berpendapat bahwa faktor emotsi wirausahawan diidentifikasi sebagai konstruk psikologis individu yang secara parsial memediasi hubungan faktor voluntaristic, faktor determiniastic dan perilaku opportunis sebagai penyebab terjadinya kegagalan berwirausaha yang dialami oleh wirausahawan pemula. Keaslian dan nilai dari studi ini terletak pada kerangka penelitian yang digunakan, yang menempatkan faktor perilaku opportunis sebagai variabel bebas yang dapat mengakibatkan kegagalan berwirausaha. Hal lainnya terletak pada adanya unsur faktor emotsi yang memediasi faktor voluntaristic, faktor determiniastic dan perilaku opportunis sebagai penyebab kegagalan berwirausaha